สภาพการบริหารบุคลากรครูชาวต่างชาติของโรงเรียนเอกชนระดับประถมศึกษาที่จัดการเรียนการสอนตามหลักสูตรกระทรวงศึกษาธิการเป็นภาษาอังกฤษ - ประภัสสร ดิษสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This Research has an objective to study on the state of foreign teacher personnel management in English programs in private primary school .The population used for this research were consist of 48 executives and 136foreign teacher from 16 school. The research was descriptive research with the tools of questionnaire with the description of checklist, data were analyzed by frequency distribution and percentage. Finding were as follow:. 1) Personnel planning found that it was performed at a high level in qualifications required for the foreign teachers was graduated with a bachelor s degree in education.2) Recruitment and selection found that it was performed at a high level in recruitment with receive news and information of the application from a school website / Facebook school, selection in interview. 3) Training and development found that it was performed at a high level in teaching techniques issues. 4) Compensation and benefits found that it was performed at a high level in welfare for medical expenses. 5) Performance appraisal found that it was performed at a high level in the objective of foreign teacher’s performance appraisal to consider for compensation, evaluation performance in quality of teaching. 6) Safety and health. found that it was performed at a high level in management handle foreign teachers that have issues and become frustrated at work by meeting with administrator directly 7) Labor relation found that it was performed at a high level in activities to build relationships between school staff for the unity of the staff within the school.